ENVIRONENTAL COMPONENT MANAGEMENT AND ENVIRONMENTAL POLLUTION PROBLEMS - Karimov Abduvoxid; Tobirov Odiljon (TADQIQOTLAR, 2025)
Abstract: Environmental pollution has become one of the most pressing global challenges, posing serious threats to human health, ecosystem stability, and sustainable development. This article provides a comprehensive review of environmental component management (ECM) as an integrated approach to addressing environmental pollution problems. The study examines the interactions between key environmental components—air, water, soil, and biological systems—and the impacts of anthropogenic activities on their degradation. Various types of pollution, including air, water, soil, chemical, and plastic pollution, are analyzed with reference to their sources, consequences, and global significance. The article also discusses management strategies such as green infrastructure, waste reduction, regulatory frameworks, and technological innovations, including bioremediation, nanotechnology, and digital monitoring systems. Case studies from different regions highlight successful management practices and policy implementations aimed at reducing environmental risks. The findings emphasize that effective environmental component management requires an interdisciplinary, technology-driven, and policy-supported framework to mitigate pollution and enhance ecological resilience. The study concludes by outlining future directions for environmental management focused on innovation, stakeholder collaboration, and sustainable governance.